(untitled) - Graves, Robert Muir (Hoboken, N.J., 2002)
Golf course construction continues to burgeon in the United States, Asia, and around the world. This book meets the needs of practicing landscape architects and other practicing professionals involved in the design or re-design of golf courses. Each classic hole is described in terms relevant to the designer including its basic design, its maintenance, and its impact on the golfer's game. Three samples accompany each classic hole illustrating varying replications and how those replications were appropriated for the new course
Keywords: Golf courses,Sân gold; Design and construction,Thiết kế và xây dựng